Pharmacological effects of Bufei Jianpi granule on chronic obstructive pulmonary disease and its metabolism in rats - Yang, Xin-Xin; Wang, Shuai; Cui, Lin-Lin; Li, Tian-Jiao; Bai, Gang; Bao, Yong-Rui; Meng, Xian-Sheng (Frontiers in Pharmacology, 2022)
This work was performed to determine the pharmacological effects of Bufei Jianpi granules on chronic obstructive pulmonary disease and its metabolism in rats. Chronic obstructive pulmonary disease (COPD), ranked as the third leading cause of death worldwide, is seriously endangering human health. At present, the pathogenesis of COPD is complex and unclear, and the drug treatment mainly aims to alleviate and improve symptoms; however, they cannot achieve the purpose of eradicating the disease. Bufei Jianpi granule (BJG) is a Chinese medicine developed by the First Affiliated Hospital of Henan University of Traditional Chinese Medicine for treating COPD. This study focuses on the pharmacological effects of BJG on COPD and its metabolism in rats, aiming to provide a scientific basis for developing BJG against COPD. A total of 72 Sprague–Dawley (SD) rats were divided into the blank group, model group, positive control group, and BJG groups (2.36, 1.18, and 0.59 g/kg). Except for the blank group, rats in other groups were administered lipopolysaccharide (LPS) combined with smoking for 6 weeks to establish the COPD model. After another 6 weeks of treatment, the therapeutic effect of BJG on COPD rats was evaluated. In the BJG (2.36 g/kg) group, the cough condition of rats was significantly relieved and the body weight was close to that of the blank group. Compared with the mortality of 16.7% in the model group, no deaths occurred in the BJG (2.36 g/kg) and (1.18 g/kg) groups. The lung tissue damage in the BJG groups was less than that in the COPD group. Compared with the model group, MV, PIF, PEF, and EF50 in the BJG groups were observably increased in a dose-dependent manner, while sRaw, Raw, and FRC were obviously decreased. Also, the contents of IL-6, IL-8, TNF-α, PGE2, MMP-9, and NO in the serum and BALF were lowered dramatically in all BJG groups. All indicators present an obvious dose–effect relationship. On this basis, the UPLC-QTOF-MS/MS technology was used to analyze characteristic metabolites in rats under physiological and pathological conditions. A total of 17 prototype and 7 metabolite components were detected, and the concentration of most components was increased in the COPD pathologic state. It is suggested that BJG has a pharmacological effect in the treatment of COPD and the absorption and metabolism of chemical components of BJG in rats exhibited significant differences under physiological and pathological conditions.